The Argumentative Nature of Ingressive Repetition in Abdullah Al-Bardouni’s "Min Ard Bilqis" (From the Land of Bilqis) Poetic Collection (Diwan) - Amer, Mohammed Muqbil Mohammed Saleh (Arts for Linguistic & Literary Studies, 2023)
This study aims to demonstrate the argumentative ingressive repetition in Yemn’s prominent poet Abdullah Al-Bardouni’s "Min Ard Bilqis" diwan, utilizing the tools of the new rhetorical analysis (discourse analysis). The study consists of an introduction and three sections. The introduction included four aspects: the first one dealt with concept of argumentation and its most important theorists; the second explored the concept of repetition according to classical and modern critics; the third focused on the concept of ingressive repetition,; the fourth examined the argumentative nature of ingressive repetition. As for the study sections, section one discussed the argumentative nature of ingressive repetition at the level of expression. Section two explored argumentative ingressive repletion at word level. Section three investigated such repletion at the instrument and device level. . The study revealed that ingressive repletion structures and functions were diverse. It was also concluded that ingressive repetition helped in articulating psychological, social, and existential dimensions in an effective artistic manner, persuading the recipient of the issues in the poems of the diwan, thus merging both the functions of delight and persuasion.